Validity and Reliability Analysis of Science Modules Using Problem-Based Learning Models Based on Ethno-STEM Assisted by Augmented Reality - Prelia Dwi Amanah; Satutik Rahayu; Gunawan Gunawan (Kappa Journal, 2025)
This study aims to analyze the validity and reliability of a Problem-Based Learning (PBL)-based science module integrated with the Ethno-STEM approach and assisted by Augmented Reality (AR) on the Motion and Force material for seventh-grade junior high school students. The module was developed as an innovative effort to improve the quality of science learning by linking local cultural contexts and the use of technology. The research method used includes validity and reliability testing involving seven expert validators, consisting of four lecturers and three science teachers, who assessed the feasibility of learning documents with five assessment scales, including the Learning Objective Flow (ATP), Learning Implementation Plan (RPP), Teaching Module, and Student Worksheet (LKPD). Validity was analyzed using Aiken's V formula, and the results of the analysis showed that all components obtained V values between 0.75 and 1.00, which was categorized as valid. Meanwhile, the inter-rater reliability test using the Intraclass Correlation Coefficient (ICC) showed an ICC value between 0.753 and 0.947. This indicates that the developed module has excellent inter-rater consistency and good to very good reliability. Therefore, this PBL-based science module, integrated with Ethno-STEM and AR, has been proven valid and reliable for use in the learning process at the junior high school level, making it a reliable learning resource.